Nancy Drew Season 2 Disc 1 - Taylor, Melinda Hsu; Landau, Noga; Brody, Jonathan; Savage, Stephanie; Schwartz, Josh 1976-; Teng, Larry; McMann, Kennedy 1996-; Lewis, Leah 1996-; Jaizani, Maddison; Kasim, Tunji; CBS DVD (Firm) (New York, NY CBS DVD, 2021)
Nancy Drew is a brilliant teenage detective whose sense of self had come from solving mysteries in her hometown of Horseshoe Bay, Maine, until her mother's untimely death derails Nancy's college plans.
The search for the midnight wraith -- The reunion of lost souls -- The secret of the solitary scribe -- The fate of the buried treasure -- The drowned woman -- Special features.
Title from container.
Originally broadcast as single episodes of a television program.
Wide screen (16x9).
Kennedy McMann, Leah Lewis, Maddison Jaizani, Tunji Kasim, Alex Saxon, Riley Smith.
Rating: Not rated.
DVD, NTSC, region 1; Dolby digital 5.1; wide screen (16x9).
Keywords: Drew, Nancy -- (Fictitious character) -- Drama; Teenagers -- Drama; Criminal investigation -- Drama; Detective and mystery television programs; Drama; Fiction television programs